Structural Properties of Ga-Doped ZnO Nanoparticles Synthesized by Co-Precipitation Process - Chongsri, K.; Pecharapa, W. (My University, 2015)
Ga-doped ZnO (GZO) nanoparticles were synthesized by co-precipitation process from starting precursors zinc dichloride (ZnCl2) and Gallium (III) nitrate hydrate (GaN3O9). The deionized (DI) water was selected as the solvent. The as-precipitated powders were calcined at different temperature of 700 and 1000 °C for 2 h. For all samples, their crystal structures were investigated by X-ray diffraction (XRD) and surface morphologies were observed by a field emission scanning electron microscope (FE-SEM). The XRD results revealed that, the crystallinity of powders increases when the calcination temperature increases. Moreover, it is noticed that the intermixture phases of ZnO and Ga2O3 occur when the Ga doping content is exceeded the solubility limit of about 10%. In addition, SEM micrographs show the decrease of particle size with increasing Ga doping content due to lattice distortion that can hinder the crystal growth of ZnO. © 2015
Keywords: Co-precipitation; Ga doped ZnO; Physical properties